Unveiling the Transformative Potential of Semi-Lean Flows on Gas Purification Units and Unlocking Energy Utilization: A Comprehensive Analysis of MDEA-Based Processes - Nnadikwe Johnson; Momoh abdulazeez adeyemi; Onyewudiala Ibeawuchi Julius (Journal Majelis Paspama, 2026)
This study explores the impact of semi-lean amine streams on energy consumption in gas purification units, focusing on Methyl Diethanolamine (MDEA)-based processes. By integrating an absorption column split stream and flash unit, we evaluate the potential energy savings and operational efficiency improvements. The results show that the split-flow design reduces amine flow rate from 4616 kmol/hr to 2622 kmol/hr, and total energy consumption decreases from 133,415,348 Btu/hr to 121,584,268 Btu/hr. Additionally, the reboiler duty is reduced from 112,744,989 Btu/hr to 104,574,974 Btu/hr. The integration of absorption column split stream and flash unit offers a promising approach to enhance energy efficiency, reduce operational costs, and minimize environmental impact